A method for extracting protein from pectin rich plant material. - Ahmad, Zalinah; Rastegari, Elham; Ismail, Maznah; Spencer, David Farringdon (2011)
The present invention relates to methods for extracting protein from plant material which is characterized by a high content of interfering compounds, specifically abundant polysaccharides like pectin. The inventive method applies a pectolytic treatment in preparation of the plant material sample prior to protein extraction. This optimized method results in high quality protein extracts compatible with further sensitive proteomic analyses specifically methods like two dimensional gel electrophoresis or mass spectrometry. The present invention further relates to the protein extracts obtained by the inventive method and the use of the inventive method in the preparation of protein samples. Also a protein extraction kit is disclosed for conducting the inventive method, as well as the use of the protein extraction kit in protein analysis and proteomics.